(untitled) (American Journal of Interdisciplinary Research and Innovation, 2025)
Success in education is only enclosed within the classroom amidst teachers and students alone. School-based management (SBM) entails the delivery of success and the structure of concrete learning outcomes. The study was participated in by 268 Grade VI pupils from 10 schools in Sto. Nino District through random sampling. Schools were identified as SBM level 3 among the 13 schools in the last SBM Regional Validation, years back 2020-2021. The survey questionnaire comprised four sections: Part I comprised pupils’ profiles, part II was on temporary suspension of SBM, including the leadership and governance, curriculum and instruction, accountability and continuous improvement, and resources management, and part III was on researcher-made questionnaire on attitudes of pupils towards learning. Part IV was a researcher-made questionnaire on challenges encountered by pupils. The content experts validated the instrument, and it was pilot-tested. Results revealed that the p-value of .511 is greater than the standard significance level of 0.05, leading to the decision to accept the null hypothesis. Hence, it can be concluded that the temporary suspension of the SBM bears no effect on the attitude of pupils in Sto. Nino District. In this study, the efficiency of school-based management relies on the stakeholders’ capacity to actualize the need and identify the existing challenges that confront the implementation. Even further, one of the indicators of the success of School-Based Management implementation lies in the students’ learning outcomes. Learners’ learning outcome depends on their attitude toward learning and their challenges in the teaching-learning process. Like the conduct of SBM, its efficiency is seen in the learning outcomes, and learning outcomes are seen in learners’ efficiency in the academic efforts.